2022
DOI: 10.3389/fcvm.2022.942485
|View full text |Cite
|
Sign up to set email alerts
|

Base excess is associated with the risk of all-cause mortality in critically ill patients with acute myocardial infarction

Abstract: BackgroundBase excess (BE) represents an increase or decrease of alkali reserves in plasma to diagnose acid-base disorders, independent of respiratory factors. Current findings about the prognostic value of BE on mortality of patients with acute myocardial infarction (AMI) are still unclear. The purpose of this study was to explore the prognostic significance of BE for short-term all-cause mortality in patients with AMI.MethodsA total of 2,465 patients diagnosed with AMI in the intensive care unit from the Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Reduced BE values, as compared to pH and lactate, could offer a more accurate estimate of metabolic acidosis related to systemic hypoperfusion in patients with severe sepsis [ 13 , 14 ]. Many studies have shown that BE is strongly associated with mortality in critically ill patients, such as those with chronic heart failure [ 9 ], trauma [ 15 ], acute kidney injury [ 16 ], and acute myocardial infarction [ 17 ]. However, there is a lack of evidence regarding the association between BE and a poor prognosis in sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced BE values, as compared to pH and lactate, could offer a more accurate estimate of metabolic acidosis related to systemic hypoperfusion in patients with severe sepsis [ 13 , 14 ]. Many studies have shown that BE is strongly associated with mortality in critically ill patients, such as those with chronic heart failure [ 9 ], trauma [ 15 ], acute kidney injury [ 16 ], and acute myocardial infarction [ 17 ]. However, there is a lack of evidence regarding the association between BE and a poor prognosis in sepsis.…”
Section: Introductionmentioning
confidence: 99%